Schmerztherapie nach thoraxchirurgischen Eingriffen - Hendrix, Holger; Kamlak, Vladimir; Prisadov, Georgi; Welcker, Katrin (Allgemein- und Viszeralchirurgie up2date, 2018)
The treatment of pain after thoracic surgery is a challenge and takes place in the individual clinics mostly according to clinic internal standards. It exists no currently valid S3 guideline for the treatment of acute perioperative and posttraumatic pain. For an effective pain treatment as well individual pain experience as the pain intensity of the various thoracic surgical procedures must be considered. Regular pain assessment with appropriate methods and their documentation form the basis for adequate and adapted pain therapy.There are a number of different pain therapy methods, non-medicamentous and drug-based methods, whose effectiveness is described in the literature partially different. For the treatment of acute postoperative pain after thoracic surgery, mainly drug-related procedures are used, except for physiotherapy as a non-medicamentous method. Increasingly, alternative procedures for the peridural catheter as a therapeutic gold standard in the treatment of pain after thoracic surgery are used. Their application can be integrated into a therapeutic algorithm.Die Behandlung von Schmerzen nach thoraxchirurgischen Eingriffen erfolgt zumeist nach klinikinternen Standards. Eine aktuell gültige S3-Leitlinie zur Behandlung akuter perioperativer und posttraumatischer Schmerzen gibt es derzeit nicht. Die unterschiedlichen Therapiemöglichkeiten akuter postoperativer Schmerzen in der Thoraxchirurgie, deren Effektivität in der Literatur sehr uneinheitlich beurteilt wird, werden in diesem Beitrag vorgestellt.
Keywords: Schmerzen nach thoraxchirurgischen Eingriffen; Schmerzintensität; chirurgisches Trauma; Algesimetrie; Schmerzmanagement; Behandlungsalgorithmus